Potential role of melatonin in autoimmune diseases. (August 2019) - Zhao, Chan-Na; Wang, Peng; Mao, Yan-Mei; Dan, Yi-Lin; Wu, Qian; Li, Xiao-Mei; Wang, De-Guang; Davis, Callan; Hu, Wenbiao; Pan, Hai-Feng
Graphical abstract: Highlights: MLT boosts Tr1 cell differentiation and suppresses Th17 cell differentiation. MLT can reduce the apoptosis of cells through decreasing the expression of Bax and preventing the loss of Bcl-2 proteins. MLT can regulate immune response through Nrf2, NFIL3, BAFF, and NF-κB. MLT may regulate the expression of microRNAs and other non-coding RNAs, ultimately alleviating autoimmune diseases Abstract: Autoimmune diseases are a broad spectrum of disorders involved in the imbalance of T-cell subsets, in which interplay or interaction of Th1, Th17 and Tregs are most important, resulting in prolonged inflammation and subsequent tissue damage. Pathogenic Th1 and Th17 cells can secrete signature proinflammatory cytokines, including interferon (IFN)-γ and IL-17, however Tregs can suppress effector cells and dampen a wide spectrum of immune responses. Melatonin (MLT) can regulate the humoral and cellular immune responses, as well as cell proliferation and immune mediators. Treatment with MLT directly interferes with T cell differentiation, controls the balance between pathogenic and regulatory T cells and regulates inflammatory cytokine release. MLT can promote the differentiation of type 1 regulatory T cells via extracellular signal regulated kinase 1/2 (Erk1/2) and retinoic acid-related orphan receptor-α (ROR-α) and suppress the differentiation of Th17 cells via the inhibition of ROR-γt and ROR-α expression through NFIL3. Moreover, MLT inhibits NF-κB signaling pathway to reduce TNF-α and IL-1β expression, promotes Nrf2 gene and protein expression to reduce oxidative and inflammatory states and regulates Bax and Bcl-2 to reduce apoptosis; all of which alleviate the development of autoimmune diseases. Thus, MLT can serve as a potential new therapeutic target, creating opportunities for the treatment of autoimmune diseases. This review aims to highlight recent advances in the role of MLT in several autoimmune diseases with particular focus given to novel signaling pathways involved in Th17 and Tregs as well as cell proliferation and apoptosis.